2018
DOI: 10.1007/s10765-018-2452-6
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Phase Equilibria, Molecular Interaction and Microstructural Studies on (N-(2-ethanol)-p-nitroaniline + N-(2-acetoxyethyl)-p-nitroaniline) Binary Mixtures

Abstract: Differential scanning calorimetry (DSC) is used to investigate the thermal properties of N-(2-ethanol)-p-nitroaniline + N-(2-acetoxyethyl)-p-nitroaniline, and their binary systems. The experimental results demonstrate that the studied binary system presents a simple eutectic behavior and the corresponding mole fraction (x eu) of N-(2-ethanol)p-nitroaniline at the eutectic point is 0.5486, whereas the temperature (T eu) is found to be equal to 363.6 K. The quality of the solid-liquid equilibria (SLE) data has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The characteristic peaks at 2878 cm −1 and 3094 cm −1 were due to the vibrations of Ar−O−CH 3 in the raw material TNBA and the C−H bond for hydrogen atoms connected to the benzene ring. We confirmed that the lowest eutectic (Figure 6(a)) for the TNBA/DNTF system showed all of the peaks for the pure components without translations, shape modification, absences, shifts or broadening of the characteristic bands; no new peaks were observed, indicating very weak intermolecular interactions between the two components of the lowest eutectic [31–33].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The characteristic peaks at 2878 cm −1 and 3094 cm −1 were due to the vibrations of Ar−O−CH 3 in the raw material TNBA and the C−H bond for hydrogen atoms connected to the benzene ring. We confirmed that the lowest eutectic (Figure 6(a)) for the TNBA/DNTF system showed all of the peaks for the pure components without translations, shape modification, absences, shifts or broadening of the characteristic bands; no new peaks were observed, indicating very weak intermolecular interactions between the two components of the lowest eutectic [31–33].…”
Section: Resultssupporting
confidence: 74%
“…In fact, the X-ray patterns of the lowest eutectic exhibited all the peaks of the pure compounds. The slight variations in the relative intensities of reflections for the pure components in the lowest eutectic can be explained by weak intermolecular interactions between the components of the eutectic [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…According to the DSC curves shown in Figure A, it is highly probable that the second solid is a cocrystal with a stoichiometric ratio of 3:2 for l -menthol:thymol (3:2 cocrystal). An analysis of the powder XRD patterns and the DSC curves in Figure shows that the solidus peaks at x thymol = 0.50 and 0.33 with onset temperatures of 271.6 and 272.7 K, respectively, represent the two eutectic points of the system. …”
Section: Resultsmentioning
confidence: 99%
“…The theoretical calculation results were almost consistent with previous experimental data. Trache et al and Chelouche et al , investigated the solid–liquid equilibria for six binary organic mixtures and observed the simple eutectic behaviors for these systems. The Wilson, NRTL, and the UNIQUAC models were employed in correlating the experimental results.…”
Section: Introductionmentioning
confidence: 99%